2011
DOI: 10.1093/eurheartj/ehr220
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-2 expression is dependent on the rs7291467 polymorphism and acts as an inhibitor of arteriogenesis

Abstract: Collectively, these results identify galectin-2 as a novel inhibitor of arteriogenesis. Modulation of galectin-2 may constitute a new therapeutic strategy for the stimulation of arteriogenesis in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…Prior studies of LGALS2 function and disease associations have been inconsistent and sometimes conflicting. Higher galectin-2 levels in monocytes and macrophages are linked to low arteriogenic response in coronary artery disease patients [53] and inflammation [54]. A case–control study in Japan first reported that the 3279C > T(rs7291467) polymorphism, which reduces galectin expression, was negatively associated with risk of myocardial infarction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of LGALS2 function and disease associations have been inconsistent and sometimes conflicting. Higher galectin-2 levels in monocytes and macrophages are linked to low arteriogenic response in coronary artery disease patients [53] and inflammation [54]. A case–control study in Japan first reported that the 3279C > T(rs7291467) polymorphism, which reduces galectin expression, was negatively associated with risk of myocardial infarction [55].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 patients with CTO were included at AMC,2 62 patients at the University Hospital Bern16 and 185 patients at the Friedrich-Schiller-University. All patients had a 100% occlusion of a coronary artery.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of collateral artery development influences the outcome after acute myocardial infarction (MI) and furthermore, in stable coronary artery disease (CAD) patients with a well-developed coronary collateral circulation it shows improved long-term survival 1 2. Thus, the stimulation of arteriogenesis is of potential clinical benefit and there is an ongoing debate on the relationship between coronary collateral artery growth (arteriogenesis) and clinical parameters like age, diabetes and medication.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-2 and LTA have been shown to be expressed in smooth muscle cells (SMCs) and macrophages in the intima of human atherosclerotic plaques, but not in quiescent or normal medial SMCs (16). Recently, one study in the Japanese population proved that the CC genotype of LGALS2 3279C>T caused high expression of galectin-2 and acted as an inhibitor of arteriogenesis in the murine hindlimb model (18). Another study in the Japanese population revealed an association between the LGALS2 polymorphism and the severity of coronary atherosclerosis through a pathological study of 1,503 consecutive autopsy cases (19).…”
Section: Introductionmentioning
confidence: 99%